Teacher Education in Brazil: Challenges and Opportunities for the Teacher in Higher Education (Interdisciplinary Studies Journal, 2024)
The social transformations that have occurred in recent decades have caused changes in teacher education in the country, especially for teachers who will work in Higher Education, considering that one of the requirements for this level is for the teacher to work with the tripod: teaching, research, and extension. Thus, this article seeks to reflect on teacher education in Brazil, with the purpose of presenting what it means to be a professor in higher education (1), the importance of the teacher’s work (2), the challenges and opportunities of this professional profile in higher education (3), and teacher management in the classroom as variables in this path to quality education (4). The methodology used was exploratory research with a bibliographic and documentary approach. It is understood that Higher Education is filled with challenges in the face of the new societal model; however, through reflection and teaching action willing to embrace transformations, it becomes possible to guarantee the first steps toward proposing improvements, minimizing the gaps in this stage of Brazilian education, such as the precarious working conditions and relationships in higher education institutions and the lack of public resources to meet professional and institutional demands.
Keywords: Higher Education; Teacher Education; Professional Profile; Brazil